The Influence of Levels of Satisfaction, Trust together with Service Quality on J&T Express Customer Loyalty in East Jakarta - Elyana, Instianti; Yusuf, Muhammad; Suardhita, Nyoman; Rahman, Aan; Martiwi, Rini (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The objective of this study is to determine the influence of service quality, trust, together with customer satisfaction on customer loyalty towards J&T Express in East Jakarta. The sample for this stidy consists of 120 respondents, selected using simple random sampling. Data collection was conducted through questionnaires. The essential tests include normality, linearity, together with multicollinearity tests. Data analysis was performed using various types of horizontal regression lines. The analysis was conducted using SPSS version 28. The results of this study indicate that, based on the t-test, service quality, trust, together with customer satisfaction are effective together with beneficial for loyal customers. Based on the results of the F-test, good service, trust, together with customer satisfaction collectively have a positive effect on customer loyalty towards J&T Express in East Jakarta. Based on several backtesting results, good service, reliability, together with customer satisfaction contribute only 67% to customer loyalty towards J&T Express in East Jakarta, while the remaining 33% reflects the influence of other variables that were not examined in this study.